COMPARISON OF THE USE OF STANDARD AIR FILTERS WITH MODIFICATION OF MACHINE PERFORMANCE - Adhiela Noer Syaief; Kurnia Dwi Artika (Scientific Journal of Mechanical Engineering Kinematika, 2020)
Motorcycle is an automotive product that is currently widely used by our society. In the fuel system there is one important part of it is a good air supply where one important component is an air filter that functions as an air filter needed in the combustion process. This research was conducted to show the effect of differences in the use of standard air filters and air filter variations on the performance of four-stroke vehicles, including emissions that occur in exhaust gas, fuel consumption as well as torque and power. This research was carried out experimentally on Yamaha Yamaha motorcycle brands 135 cc. Analysis of the data used is descriptive statistics with data displayed in graphical form. The results of the exhaust gas emission test on a standard air filter CO levels are better, but the HC and CO2 levels in the air filter variations are better. Furthermore, the maximum torque at the standard air filter is higher than the variation of the air filter, but for maximum power at the variation of the air filter is higher at 9.16 HP with 8.79 HP. Then the fuel consumption in the standard air filter is lower than the variation of air filters.